2006
DOI: 10.2134/jeq2005.0225
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physical Properties to Predict the Effects of Tillage Practices on Organic Matter Dynamics in Three Illinois Soils

Abstract: This work builds on a previous study of long-term tillage trials that found use of no-tillage (NT) practices increased soil organic carbon (SOC) sequestration at Monmouth, IL (silt loam soil) by increasing the soil's protective capacity, but did not alter SOC storage in DeKalb, IL (silty clay loam), where higher clay contents provided a protective capacity not affected by tillage. The least limiting water range (LLWR), a multi-factor index of structural quality, predicted observed soil CO2 efflux patterns. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…Yoo et al (2006) concluded that the use of zero tillage practices only enhances physical protection of SOC where soil bulk density is relatively high (approximately 1.4 g cm −3 ) and when the use of zero tillage management reduces the volume of small macropores (15-150 µm), thought to be important for microbial activity. This notion is supported by the findings of Strong et al (2004) who observed rapid decomposition of C in the pores with neck diameters between 15 and 60 µm.…”
Section: The Influence Of Tillage Practice On Soil Organic Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al (2006) concluded that the use of zero tillage practices only enhances physical protection of SOC where soil bulk density is relatively high (approximately 1.4 g cm −3 ) and when the use of zero tillage management reduces the volume of small macropores (15-150 µm), thought to be important for microbial activity. This notion is supported by the findings of Strong et al (2004) who observed rapid decomposition of C in the pores with neck diameters between 15 and 60 µm.…”
Section: The Influence Of Tillage Practice On Soil Organic Carbonmentioning
confidence: 99%
“…There may be a threshold value for bulk density that must be exceeded before pore-dependent processes are constrained and protect SOC. By refining our understanding of the interactions between management, pore structure and SOC mineralization, we should be able to predict the influence of tillage practices on SOC sequestration (Yoo et al, 2006).…”
Section: The Influence Of Tillage Practice On Soil Organic Carbonmentioning
confidence: 99%
“…The effect of soil strength on root distribution has been observed to be stronger for grass species than for tap-rooted species [34]. Lack of oxygen may also limit root growth, particularly in fine-textured soils [35]. If root growth is limited by low oxygen, RLDs could be expected to be low in areas where the percentage of water-filled pore space (%WFPS) exceeds 60% [36].…”
Section: Introductionmentioning
confidence: 99%
“…da Silva and Kay (1997) showed that plant growth is more vulnerable to environmental conditions (such as climate and rainfall) in soils which have a narrow LLWR than those soils, which have a wide LLWR. Yoo et al (2006) consider whether LLWR and pore size characteristics could explain the influence of notill practices on the increase of soil organic carbon sequestration. They concluded that pore size distribution may provide useful information about the mechanistic relationship between soil structure and microbial activity but LLWR is easier to determine than the pore size distribution as long as appropriate pedotransfer functions, which rely on soil water retention and mechanical resistance curves, are available.…”
Section: Introductionmentioning
confidence: 99%